Ms44-SPT: Unique genetic technology simplifies and improves hybrid maize seed production in sub-Saharan Africa - Collinson, Sarah; Cairns, Jill E.; Ndlala, Lucia; Deonovic, Benjamin; Ligeyo, Dickson; Albertsen, Marc; Chivasa, Walter; Mashingaidze, Kingstone; Olsen, Michael S.; Tadesse, Berhanu T.; Prasanna, Boddupalli M. (Springer, 2024)
Hybrid maize seed production in Africa is dependent upon manual detasseling of the female parental lines, often resulting in plant damage that can lead to reduced seed yields on those detasseled lines. Additionally, incomplete detasseling can result in hybrid purity issues that can lead to production fields being rejected. A unique nuclear genetic male sterility seed production technology, referred to as Ms44-SPT, was developed to avoid hybrid seed loss and to improve the purity and quality of hybrid maize production. Hybrid seed yield reduction following detasseling can be attributed to leaf loss. Our analyses showed an average 2.9 leaves are lost during the detasseling process, resulting in a seed yield reduction of 14.0%. These findings suggest that deploying the Ms44-SPT technology would avoid this seed yield loss. By simplifying hybrid production and increasing seed yields, Ms44-SPT could help drive hybrid replacement, providing smallholder farmers with better access to improved hybrids.